(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background: Modern medical administration has pivoted toward the Patient Experience (PX) as the definitive metric for institutional success. This shift moves beyond traditional clinical outcomes to evaluate holistic service quality, recognising that administrative efficiency and environmental safety are now critical pillars of healthcare delivery. Objective: This study analyses operational bottlenecks and infrastructure deficits in Gujarat’s healthcare facilities to bridge the gap between perceived service quality and National Building Code safety standards while evaluating their impact on patient loyalty and accreditation. Methodology: This research analysed a dataset of 340 respondents across Gujarat using a cross-sectional survey, the SERVQUAL framework, and regression analysis to determine the impact of environmental factors on OPD and IPD patient satisfaction. Findings: The data identifies a significant "Service-Safety Divergence." While clinical nursing satisfaction reached a high of 88%, critical deficits were identified in emergency wayfinding (55%) and waittime management (46%). Regression results indicate that environmental factors—specifically signage clarity and potable water access—carry a disproportionate weight in patient loyalty scores, revealing a systemic reliance on human capital to mask infrastructural weaknesses. Conclusion: To resolve these gaps, the study advocates for digital queue management and trilingual safety wayfinding. Actionable strategies are provided to align Gujarat’s healthcare infrastructure with international quality benchmarks, ensuring long-term operational excellence.